Brown Root Rot Disease of Phyllanthus myrtifolius The Causal Agent and Two Potential Biological Control Agents - Leung, Ka-Tung (Plant disease, 2020)
Brown root rot (BRR), caused by Phellinus noxius (Corner) G. Cunningham, occurs on over 200 species of plants, especially woody trees and shrubs. Ceylon myrtle (Phyllanthus myrtifolius [Wight] Müll.Arg.), a common hedge plant, was recently observed to be infected with BRR. Disease diagnosis was performed by completing Koch's postulates, and Ceylon myrtle was confirmed to be a new host of P. noxius. Typical symptoms of BRR were observed, including reduction in leaf size, dieback of branches, and suspended growth of young leaves. A disease severity index was used to quantify BRR in this study. Compared with Malabar chestnut, Ceylon myrtle was relatively resistant to BRR. Surprisingly, phylogenetic analysis of the ITS and 28S sequences revealed that isolates identified as P. noxius from Taiwan and many other countries were clustered in the same clade but separate from the clade comprising isolates from China, which were designated Pyrrhoderma noxium based on P. noxius. Therefore, to temporarily distinguish these pathogens, the former clade was designated GPN (global P. noxius), whereas the latter clade was designated CPN (China Py. noxium). In biocontrol assays, Streptomyces padanus and Bacillus sp. were selected for BRR control of Ceylon myrtle. Disease severity was reduced from 0.51 to 0.37 by S. padanus and to 0.14 by Bacillus sp. in greenhouse trials. In addition, the two biocontrol agents, especially S. padanus, exhibited good growth-promoting effects on cuttings of Ceylon myrtle. With these double advantages, S. padanus and Bacillus sp. have great potential to control BRR in practical applications